Progressive failure mechanism in granular materials subjected to an alternant active and passive trapdoor. (May 2021) - Zhao, Yu; Gong, Quanmei; Wu, Yaojie; Tian, Zhiyao; Zhou, Shunhua; Fu, Longlong
Abstract: Underground structures/machines may undergo upward and downward movements due to construction activities or environmental changes. The ground state could be significantly disturbed by previous construction and subsequent structural movements. In this study, alternant active and passive trapdoor tests simulating the ground disturbance were conducted to explore the progressive failure of the overlying soil using a self-developed particle image velocimetry system. The evolution of load, characteristic of soil movement, propagation of shear bands, evolution of failure zones, and volumetric change behavior were obtained and interpreted to better understand the progressive failure of soil. Four typical progressive failure modes (e.g., local punching shear failure and tensile failure) corresponding to different disturbance paths were identified and compared with the classical active or passive arching mechanisms. The results showed that the degradation of the arching effect will occur, whether in subsequent active or passive state. Prediction of the load on the structure based on classical arching mechanism could significantly deviate real load. Meanwhile, a much larger surface settlement and settlement range were observed compared to that of classical active state with the same ground loss value. Further, the effect of the previous ground disturbance on the progressive failure mechanisms was interpreted by the dilative and contractive behavior of the overlying soil. This study provides a profound basis for estimation of the life-cycle load on underground structures and prediction of ground deformation in view of the ground elevation or erosion collapse caused by subsequent engineering activities and changes in the surrounding environmental condition.